Sinonasal Hemangiopericytoma: A Case Report - Aliasghar Peyvandi (Iranian Journal of Medical Sciences, 2010)
Hemangiopericytoma is a vascular tumor that is rarely seen inthe nose and paranasal sinuses. Biological behavior of thesetumors is not completely known, and their natural history isnot predictable. This case report presents a patient with a sinonasalhemangiopericytoma. Diagnosis and management ofthese uncommon tumors is discussed.